Physicochemical and nutritional properties of starches from nine Canadian‐grown peas compared with six commercial starches. Issue 3 (19th December 2021) - Lu, Zhan‐Hui; Lu, Yiting; Donner, Elizabeth; Liu, Qiang; Bing, Dengjin
Abstract: The physicochemical properties and nutritional fractions of the starches isolated from nine Canadian‐grown peas, including marrowfat, green, and yellow pea types, were studied and compared with six commercial starches, to explore the unique properties of these pea starches. These nine pea starches were found to have high apparent amylose content (marrowfat peas, 51.3%–51.6%; yellow peas, 50.6%–53.8%; and green peas, 49.9%–54.2%) and a higher tendency than most commercial starches to retrograde. Although their physicochemical properties were not drastically different, a green pea variety, Limerick, stood out for its significantly high apparent amylose content (54.2%) and also the highest resistant starch (RS) content after cooking (29.5%), the latter even comparable with a commercial high amylose corn starch (29.8%). Principal component analysis indicated that amylose content, amylose leaching, and Rapid Visco Analyzer (RVA) parameters at the cooling stage are significantly positively correlated to the starch nutritional fractions of cooked samples. Cluster analysis showed a clear pattern that the RS content in cooked starches increased with the increasing amylose content in these starch samples. In general, these pea starches were rich in slowly digestible starch and high in RS after cooking (>16%). This study highlighted the unique properties of these pea starches, including their high amylose content, and ease of gelatinization yet strong tendency toward retrogradation, which resulted in superior final pasting viscosity and high RS content; thus, these pea starches could be the best alternative to commercial high amylose starches, to address the latter's deficiencies in pasting properties when applying in gel‐based low glycemic index (GI) foods.